HerMES: SPIRE galaxy number counts at 250, 350, and 500 μ m - Oliver, S; Wang, L; Smith, A; Altieri, B; Amblard, A; Arumugam, V; Auld, R; Aussel, H; Babbedge, T; Blain, A; Bock, J; Boselli, A; et al. (2010)
Emission at far-infrared wavelengths makes up a significant fraction of the total light detected from galaxies over the age of Universe. Herschel provides an opportunity for studying galaxies at the peak wavelength of their emission. Our aim is to provide a benchmark for models of galaxy population evolution and to test pre-existing models of galaxies. With the Herschel Multi-tiered Extra-galactic survey, HerMES, we have observed a number of fields of different areas and sensitivity using the SPIRE instrument on Herschel. We have determined the number counts of galaxies down to ~20 mJy. Our constraints from directly counting galaxies are consistent with, though more precise than, estimates from the BLAST fluctuation analysis. We have found a steep rise in the Euclidean normalised counts <100 mJy. We have directly resolved ~15% of the infrared extra-galactic background at the wavelength near where it peaks. © 2010 ESO.